Diversity of xerotolerant and xerophilic fungi in honey - E. Rodríguez-Andrade; A. M. Stchigel; A. Terrab; J. Guarro; J. F. Cano-Lira (IMA Fungus, 2019)
Abstract Fungi can colonize most of the substrata on Earth. Honey, a sugary food produced by bees (and other insects) has been studied little in terms of its fungal diversity. We have surveyed and evaluated the presence of xerotolerant and xerophilic fungi in a set of honey bee samples collected from across Spain. From 84 samples, a total of 104 fungal strains were isolated, and morphologically and phylogenetically characterized. We identified 32 species distributed across 16 genera, most of them belonging to the ascomycetous genera Aspergillus, Bettsia, Candida, Eremascus, Monascus, Oidiodendron, Penicillium, Skoua, Talaromyces and Zygosaccharomyces. As a result of this survey, eight new taxa are proposed: i.e. the new family Helicoarthrosporaceae, two new genera, Helicoarthrosporum and Strongyloarthrosporum in Onygenales; three new species of Eurotiales, Talaromyces affinitatimellis, T. basipetosporus, and T. brunneosporus; and two new species of Myxotrichaceae, Oidiodendron mellicola, and Skoua asexualis.